STRUKTUR TULANGAN RINGAN UNTUK BANGUNAN SEDERHANA - Gazalba, Zaedar; Kamase, Giska Ayu Pradana Putri; Raissilki, Muhammad Iqbal; Indriani, Ni Ketut Ayu Intan Putri Mentari; Anantama, Aldhi Nugraha (Universitas Mataram, 2025)
The series of Lombok earthquakes in 2018 caused huge losses of life and property. There were 460 fatalities, 7,733 injured, 417,529 displaced. In addition, the earthquake also damaged 71,962 houses, 671 educational facilities, 52 health facilities, 128 worship facilities and infrastructure such as roads, bridges, drainage channels, irrigation channels, dams, etc. were recorded as having suffered severe damage. In repairing houses, the Central Government has budgeted more than 5.1 trillion Rupiah. Based on the results of field investigations, it was found that generally the buildings that were severely damaged (collapsed) were residential buildings with brick wall construction and most of them used reinforced concrete columns and beams. This can happen because the construction system carried out by the community and especially the workers does not meet the requirements for concrete and reinforcement quality standards. To prevent this from happening again, it is deemed necessary to provide counseling on the lightweight reinforcement construction system that meets construction requirements so that the strength of the building can be more resistant to earthquakes.